MODEL PENDIDIKAN BERBASIS KHALIFAH FIL ARDH DI SPMAA: INTEGRASI EKOLOGI ISLAM DAN KEMANDIRIAN EKONOMI SEBAGAI FONDASI PERADABAN BERKELANJUTAN - Thooriq Nur Hidayat; Naufal Nadhif Hibatullah (Ikatan Dosen Menulis, 2026)
This research aims to analyze the Khalifah fil Ardh-based education model at SPMAA Lamongan Islamic Boarding School as an integrative solution to the ecological crisis and economic dependence of Islamic educational institutions. Utilizing a qualitative method with a case study approach, data were collected through participatory observation and in-depth interviews with practitioners. The results show that SPMAA has successfully translated the theology of vicegerency (khalifah) into concrete managerial practices through three main instruments: 1) Spiritual HR management based on the Tenaga Penyayang Umat (TPU) philosophy and the Pegawai Gaji Akherat (PGA) work ethos, which creates extreme operational efficiency; 2) Radical financial independence through a